Benefit Programs Rural Agribusiness Effort (PUAP) For Production To Stock Down Rubber At Sembawaâs District Banyuasinâs Regency - Saputra, Angga; Batubara, Mustopa Marli; Abubakar, Rafeah (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2015)
Benefit Programs Rural Agribusiness Effort (PUAP) For Production To Stock Down Rubber At sembawas district Banyuasins Regency. To the effect this research is subject to be know how role of rural agribusiness effort program (PUAP) in increase rubber seed production. Executed research at sembawas district Banyuasins Regency on month of June 2015. Observational method that is utilized is case study (case study) with farmer respondent that labours to stock down rubber. Meanwhile pull method samples thatis utilized is census method with sample amount 20 person. Methodic data collecting that is utilized is Observation and Interview method, there is data even that gathered consisting of skunders primary and data data. Methodic data processing that is utilized in this research is descriptive method with kualitatifs approaching. With stage earlying to figure or depicts observational object situation base observable fact or as it were mark sense, hereafter new dianalisis descriptive ala. Result observationaling to point out that with marks sense capital loan of Rural Agribusiness Effort Program (PUAP) farmer perceives really assisted deep usahatanis activity because farmer can add usahatanis capital to pembibitan rubber and rubber seed production even progressively increases.